IS STRUCTURAL ECONOMIC TRANSFORMATION FROM AGRICULTURE TO INDUSTRY OCCURRING ON SULAWESI ISLAND? - Teguh Endaryanto; Lestari Gita Nur'aini; Muhammad Irfan Affandi (Universitas Sebelas Maret, 2026)
Structural economic transformation, particularly the shift from agriculture-based activities toward industrial and service-oriented sectors, is a key indicator of regional development. This study aims to examine whether structural transformation from the agricultural sector to other economic sectors has occurred on Sulawesi Island, Indonesia. The study employs secondary data in the form of Gross Regional Domestic Product (GRDP) at constant prices for Sulawesi Island and its provinces during the period 2010–2024, obtained from Statistics Indonesia (BPS). A descriptive quantitative approach is used to analyze changes in sectoral contributions to regional economic structure. The results indicate that Sulawesi Island has experienced a decline in the contribution of the agricultural sector, accompanied by an increase in the manufacturing, information and communication, and trade sectors. The direction and magnitude of structural transformation vary across provinces, resulting in three distinct transformation patterns: (1) a shift from the primary sector toward secondary and tertiary sectors, (2) a concentration of transformation toward the secondary sector, and (3) a shift toward the tertiary sector. These findings suggest that structural transformation in Sulawesi Island is occurring unevenly across regions and is strongly influenced by regional economic characteristics and development policies. The results provide important insights for regional development planning and sectoral policy formulation in Sulawesi Island.